2008
DOI: 10.1111/j.1464-410x.2008.07638.x
|View full text |Cite
|
Sign up to set email alerts
|

Features and outcomes of patients with grade IV renal injury

Abstract: OBJECTIVE To evaluate the clinical features and outcomes of patients who presented with grade IV renal trauma to our urban level I trauma hospital and to further refine the absolute indications for exploration and determine the outcomes of conservative management. PATIENTS AND METHODS In all, 77 patients with grade IV traumatic renal injuries presented to our emergency department between October 1997 and October 2006. A prospective trauma database including these patients was analysed to determine the patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 9 publications
1
35
0
4
Order By: Relevance
“…Nephrorrhaphy was associated with the highest rate of complications. Similarly, Shariat et al 26 showed nonsignificantly different rates of complications between NOM patients (28%) and IO patients (13%) with grade IV BRIs. Obviously, these results may be misleading because renal-related complications are harder to develop after nephrectomy, and one could argue that the ultimate complication is the loss of the kidney.…”
Section: Discussionmentioning
confidence: 89%
“…Nephrorrhaphy was associated with the highest rate of complications. Similarly, Shariat et al 26 showed nonsignificantly different rates of complications between NOM patients (28%) and IO patients (13%) with grade IV BRIs. Obviously, these results may be misleading because renal-related complications are harder to develop after nephrectomy, and one could argue that the ultimate complication is the loss of the kidney.…”
Section: Discussionmentioning
confidence: 89%
“…[1,4] Son yıllarda, tanı ve takip yöntemlerinin gelişmesi ve bu konuda hekimlerin tecrübelerin artmasıyla daha az invaziv tedavi yöntemleri kullanılmaya başlanmıştır. [4] Solid organ yaralanmalarındaki ameliyatsız yöntemle tedavinin başarı oranları günümüzde %90'ların üzerine çıkmıştır.…”
Section: Discussionunclassified
“…[1,4] Son yıllarda, tanı ve takip yöntemlerinin gelişmesi ve bu konuda hekimlerin tecrübelerin artmasıyla daha az invaziv tedavi yöntemleri kullanılmaya başlanmıştır. [4] Solid organ yaralanmalarındaki ameliyatsız yöntemle tedavinin başarı oranları günümüzde %90'ların üzerine çıkmıştır. [8][9][10] 1951 yılında King ve Schumacker'in postsplenektomi sepsisini göstermeleri ve çocuk cerrahlarının dalağı mümkün olduğun-ca koruma çalışmalarıyla başlayan bu süreçte başlangıçta çe-şitli kısıtlamalara neden olan belirsizlikler ve kuşkular her gün çoğalan başarılı sonuçların görülmesiyle artık kaybolmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Contrarily, the AUA recommends observation for hemodynamically stable patients regardless of AAST grade, due to interobserver variability regarding classification of grade 4 and 5 injuries (Grade B, AUA). With the increasing evidence of excellent outcomes of conservative management for correctly classified grade 4 injuries [16,17], there have been proposals to re-classify grade 4 and 5 injuries [18,19]; this would clarify the ambiguities of defining these injuries and may allow for more successful management decisions.…”
Section: Introductionmentioning
confidence: 99%